Comprehensive Metabolomics in Mouse Mast Cell Model of Allergic Rhinitis for Profiling, Modulation, Semiquantitative Analysis, and Pathway Analysis - Akshay Suresh Patil; Yan Xu (Biomolecules)
Allergic rhinitis affects millions globally, causing significant discomfort and reducing the quality of life. This study investigates the metabolic alterations in murine mast cells (MC/9) under allergic rhinitis conditions induced by lipopolysaccharide (LPS) stimulation, employing UHPLC-QTOF-MS-based untargeted and targeted metabolomics. The analysis identified 44 significantly regulated metabolites, including histamine, leukotrienes, prostaglandins, thromboxanes, and ceramides. Key metabolic pathways such as arachidonic acid, histidine, and sphingolipid metabolisms were notably modulated. The study further examined the therapeutic effects of triprolidine and zileuton, demonstrating their capacity to reverse LPS-induced metabolic shifts. Triprolidine primarily modulated histidine and sphingolipid metabolism, while zileuton targeted arachidonic acid and sphingolipid metabolism. These findings underscore the utility of metabolomics analysis in elucidating the complex biochemical pathways involved in allergic rhinitis and highlight the potential of metabolomics for evaluating therapeutic interventions. This study enhances our understanding of mast cell metabolism in allergic responses and provides a robust model for assessing the efficacy of anti-allergic agents, paving the way for more effective treatments.